PROBLEMATIKA PERGANTIAN ANTAR WAKTU ANGGOTA DPRD KABUPATEN PANIAI MENURUT UU 17 TAHUN 2014 - Eren Arif Budiman (Universitas Stikubank, 2023)
In order to ensure the strength and existence of political parties in parliament, political parties have authority over their cadres who become people's representatives. One of the authorities of political parties over people's representatives is the Time Shift (PAW), which is used by political parties against members of the People's Legislative Assembly who come from political parties. As a result, political parties have the authority to dismiss political cadres who are found to have violated party rules or the constitution. This study will look at how problematic the Inter-Time Change of DPRD members in Paniai Regency is under Law Number 17 of 2014. The research method employed is normative research, which is defined as research based on theoretical studies, principles, or other existing written legal regulations that will then be examined from various perspectives such as theory, history, philosophy, comparison, structure and composition, scope and material, consistency, general explanations, and chapter by chapter. The Prosperous Justice Party faction encountered difficulties in implementing the AMOS KEGIBUI MUYAPA Inter-Time Alternation mechanism in the Paniai Regency DPRD. AMOS KEGIBUI MUYAPA's problems and delays are contrary to statutory regulations; therefore, Time Shift (PAW) must be carried out in order to increase the strength and existence of the Prosperous Justice Party and the opposition in parliament in order to build political strength in the face of the 2024 general election.